Crop Breed Genet Genom. 2020
DOI: 10.20900/cbgg20200016
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Genomic Selection and Integrating “Omics” Data for Disease Evaluation in Wheat

Abstract: Diseases are among the most important limiting factors for wheat production. Breeding for fungal diseases of wheat, primarily for rusts and Fusarium head blight (FHB), are major resource consuming activities in most breeding programs which prevent breeders from focusing entirely on improving yield. Breeding for these diseases is challenging because resistance is inherited mostly in a quantitative fashion and is greatly influenced by weather conditions. Recent advances in genomics, phenomics and big-data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 141 publications
(175 reference statements)
0
11
0
Order By: Relevance
“…One major target of genomic selection is the genetic improvement of resistance against fungal diseases [2]. Within this framework the resistance of wheat against Fusarium head blight (FHB) is probably one of the most thoroughly studied pathosystems [3]. FHB of wheat is induced by several species among which Fusarium graminearum, Fusarium culmorum, and Fusarium sporotrichioides are the most prominent and agronomically important causal agents conferring large losses in grain yield and contamination of harvested grain with mycotoxins [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One major target of genomic selection is the genetic improvement of resistance against fungal diseases [2]. Within this framework the resistance of wheat against Fusarium head blight (FHB) is probably one of the most thoroughly studied pathosystems [3]. FHB of wheat is induced by several species among which Fusarium graminearum, Fusarium culmorum, and Fusarium sporotrichioides are the most prominent and agronomically important causal agents conferring large losses in grain yield and contamination of harvested grain with mycotoxins [4].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the genome, other biological strata like the transcriptome and metabolome can serve as an alternative or complement to genomic data in predictive breeding [14,15]. However, the latter two "omics"-methods have not been assessed for predicting FHB resistance in wheat until now [3]. Albeit metabolites can be considered closest to the actual phenotype, and in theory unite the previous biological strata, on the other hand they are also subject to practical constrains like fast turn-over rates.…”
Section: Introductionmentioning
confidence: 99%
“…This population was the subject of a GS study with encouraging results (Nyine et al, 2018). In wheat, Haile et al (2020) reported that it was possible to extract the useful alleles in the germplasm population. For this purpose, prediction error variance (PEV) and generalized coefficient of determination (CD) methods have been reported to optimize the TP from germplasm collection.…”
Section: Design Of the Training Population From Germplasm And Clonall...mentioning
confidence: 99%
“…This population was the subject of a GS study with encouraging results ( Nyine et al., 2018 ). In wheat, Haile et al. (2020) reported that it was possible to extract the useful alleles in the germplasm population.…”
Section: Perspectives To Succeed Gs On Polyploid Cropsmentioning
confidence: 99%
See 1 more Smart Citation